2009
DOI: 10.1111/j.1523-5378.2009.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacters and Extragastric Diseases

Abstract: For two decades, Helicobacter pylori has been considered as the culprit in many extragastric manifestations. However, for several of these supposed associations the hypothesis of an etiological role has not yet been fully investigated. This may be due to a series of factors linked to the epidemiological features of the studies and to the diseases investigated. This review attempts to highlight the main reported associations of H. pylori with extragastric manifestations during the last year. The most convincing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 108 publications
(109 reference statements)
0
44
0
4
Order By: Relevance
“…H. pylori is suggested to be related with low grade inflammation [15]. This low grade inflammation regarding H. pylori infection is associated with diabetes mellitus and atherosclerosis [16, 17]. CagA is one of the most virulent factors of H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori is suggested to be related with low grade inflammation [15]. This low grade inflammation regarding H. pylori infection is associated with diabetes mellitus and atherosclerosis [16, 17]. CagA is one of the most virulent factors of H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have shown that diabetic angiopathy could damage mucosal integrity and lead to more severe ulcers, which made it more difficult to halt hemorrhage in patients with peptic ulcers (24,26). Moreover, some studies have demonstrated that DM affects the associations between Helicobacter pylori infection and peptic lesions (41)(42)(43)(44). Furthermore, animal studies have shown that diabetes increases the release of pro-inflammatory cytokines and attenuates angiogenesis, which results in impaired ulcer healing (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery in 1983 that the stomach could be colonized by bacteria [3], sufficient evidence has accumulated implicating H. pylori as a pathogen intimately related to benign stomach diseases, such us chronic gastritis and duodenal and gastric peptic ulcers [3], and malignant diseases, for example gastric cancer [4] and gastric MALT lymphoma [5]. Furthermore, during the last three decades following the discovery [3], approximately 50 extragastric diseases have been reported in medical specialties such as cardiology, dermatology, endocrinology, obstetrics and gynecology, pneumology, neurology, odontology, ophthalmology, otorhinolaryngology, pediatrics, and hematology [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], the last of which is the subject of this review.…”
Section: Introductionmentioning
confidence: 99%